Who rules the world? - Morgan, Dennis (Foresight: Volume 17, Issue 2., 2015)
Who rules the world? Is there an identifiable global ruling power? If so, is this global rulingpower derived from the will and consent of the billions of people that inhabit this planet? If not, then from what source is this power derived? On the other hand, if there is no identifiable globalruling power, as many assume, then are the people of this world free to chart their collective future? If not, why not? To what degree does the autonomous nature of the technological societydetermine the future of humanity? Is it possible to realize global democracy and sustainability? If so, then how can.